Kindness, Listening, and Connection: Patient and Clinician Key Requirements for Emotional Support in Chronic and Complex Care. (April 2022) - Bradshaw, Jane; Siddiqui, Nazlee; Greenfield, David; Sharma, Anita
Emotional support for patients is critical for achieving person-centered care. However, the literature evidences an ongoing challenge in embedding emotional support within current health services. This study aimed to investigate the strategies to embed emotional support from the perspectives of patients and clinicians. This is an exploratory qualitative study that collected data through focus group discussions (FGDs) and interviews from 11 patients, 2 carers, and 7 clinicians in the multi-disciplinary care teams in an outpatient complex and chronic care setting in New South Wales, Australia. The FGDs and interviews were recorded, transcribed, and thematically analyzed. Three main themes emerged from the experience of both the patients and clinicians: (1) warmth and kindness, (2) deep listening, and (3) social connection in the process of treatment. Clinicians' and patients' shared experience of these themes was key to embed emotional support in care. Practical strategies including promoting shared understanding of emotional support, enhancing provider's capability to deliver emotional support, and building patient's networking opportunities in treatment processes were discussed to facilitate emotional support in patient care and health services.